A framework for effective energy management in a chemical compound plant - Nadarajah, Jayaseelan (2017)
The electrical energy requirements by industry has increased tremendously as reported by the Malaysian electrical energy utility company, Tenaga Nasional Berhad. This increase has forced engineers to devise initiatives to overcome the possible shortages. Emphasis should thus be given to alter the consumption patterns. The impact to the environment and the conservation of energy should also be addressed. Effective energy management reduces operating costs of industries. In Malaysia, industries have already been advised, some two decades ago to perform energy saving measures. This exercise should be performed with the intention of becoming more competitive, apart from lowering operating costs and conserving the environment. This is very important for economic growth in a country. Resources utilizing low cost options are being utilized to ensure adequate electrical energy supplies. Awareness programs are being implemented in industry to discourage wastage, but to encourage efficient and cost effective operations. This research also discovered that currently the chemical compound industry lacked a well-structured and a systematic method for analysis of energy consumption. The demand for energy in this industry continues to grow at a staggering 7% per annum, according to the Ministry of International Trade and Industry of Malaysia. This is notwithstanding the expected increase in tariff, by approximately 10% before the year 2020. Moreover, the current ISO 50001 Standards on Energy Management were deemed as only a guide but not a complete reference for the said industry. Therefore, this research embarked to rank the parameters that contributed to energy efficiency in industry and subsequently to develop a framework and to validate it upon implementation in industry. The methodology used in this research involved data collection and analysis, which utilized graphical methods, tables and charts and a questionnaire design. The major findings of this research are, amongst others, the said industry’s acceptance of the proposed framework and the reduction of electrical energy consumption, and hence greenhouse gas (GHG) emission upon implementation of the recommended projects. The results of this research also indicate very clearly that the integration between maintenance, human resources and production. are vital for improved and optimized consumption of energy. This research will encourage industrialists to consider the various opportunities available to manage energy in industry utilizing a well-structured and engineered methodology and to consider energy management initiatives seriously.